EKSPLORASI ETNOMATEMATIKA DALAM PERMAINAN TRADISIONAL LOMPAT TALI PADA PEMBELAJARAN BERHITUNG SISWA KELAS I SEKOLAH DASAR - Fajrul Izza (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This study aims to investigate the use of ethnomathematics in the traditional game of jump rope in learning arithmetic for grade I students in elementary schools. The research method used is a qualitative approach with data collection techniques through observation, interviews and documentation. Through the use of ethnomathematics, students are exposed to learning experiences that include cultural aspects and traditional values ​​in a mathematical context. The results of this research show that the use of ethnomathematics in the traditional game of rope jumping is very effective in increasing students' understanding of the concept of counting. Students are actively involved in this game, practicing their counting skills by observing jump patterns, counting the number of jumps, and comparing numbers. In doing so, they not only develop math skills, but also gain a deeper understanding of their culture and traditions.